Traditional medicinal knowledge and use of Ubar Kampung among local healers in Tatar Sunda, West Java, Indonesia (Asian Journal of Ethnobiology, 2025)
Abstract. Febriyanti RM, Susilawati Y, Tjitraresmi A, Muhaimin. 2025. Traditional medicinal knowledge and use of Ubar Kampung among local healers in Tatar Sunda, West Java, Indonesia. Asian J Ethnobiol 8: 202-221. In Sundanese communities (West Java, Indonesia), traditional medicine (Ubar Kampung) remains central to primary health care. This study aims to document medicinal plant use by local healers and quantify cultural salience-that is the significance of a plant in the cultural practices and beliefs of the Sundanese people. Studies were conducted between 2017 and 2019 using semi-structured interviews with 52 purposively selected key informants (healers, elders, traditional birth attendants) across five Sundanese villages. We recorded 111 species from 54 families. Leaves were the most frequently used part, and decoction was the predominant preparation. Curcuma longa and Kaempferia galanga had the highest RFC (1.00) and high UV (4.07 and 4.15). Digestive disorders showed the strongest agreement (ICF?=?0.88), with Psidium guajava cited unanimously for diarrhea (FL?=?100%). Musculoskeletal conditions also showed high consensus (ICF?=?0.87), particularly for K. galanga. Ubar Kampung represents a resilient medical system, with culturally salient species that align with reported pharmacological activities. Prioritized taxa (such as K. galanga, C. longa, and P. guajava) warrant targeted pharmacological and conservation action. Documenting this knowledge supports sustainable use and culturally appropriate integration with regional health services and paves the way for future research and discoveries on plant knowledge and use among healers in the Tatar Sunda Region, West Java, Indonesia.
Keywords: Ethnobotany, informant consensus factor, relative frequency of citation, Sundanese traditional medicine, use value